Framing Women Politician in Democratic Environment: A Study of Megawati Soekarno Putri and Hillary Clinton - Nurlita Hapsari (Rubikon : Journal of Transnational American Studies, 2017)
This research was aimed to examine how media coverage produces particular framing toward women politician during presidential campaign as well as the significance behind the framings toward gender conception in Indonesia and America. Media holds a vital political role as it helps shaping people’s opinion over particular issues and figures. As media coverage toward particular candidates can profoundly affect election outcomes, it is interesting to see how media presents two women figures who ran for presidential race.This is a qualitative research. The main sources of data are articles gathered from eight online-based news outlets. There are two kinds of data; primary and secondary data. For analysis on Megawati Soekarno Putri, the primary data are articles from Detik, Liputan6, and Tempo. While for Hillary Clinton, the data are articles from The New York Times, USA Today, The Washington Post, The Los Angeles Times, and The Wall Street Journal. The secondary data are all selected works or research related to the topic such as reference books and journals.This research was done under the framework of American Studies. Since American Studies is interdisciplinary, it involves various theories and disciplines. This research uses gender theory to observe how media shape the image of women politician through their news coverage. Critical discourse analysis is used to explore the significance of media framing on women politician to society’s conception of women’s gender roles. Then, framing theory is important to analyze media’s method and ideology in constructing the facts within the coverage.In the research analysis, it is found that there are various framings used by media to describe Hillary Clinton and Megawati Soekarno Putri. While media in two countries have different focuses, news coverage on both media share the same stereotyping woman theme such as emphasis on physical appearance and family association. In the end, learning from the media framing toward woman politician, we can conclude that despite feminist achievement in many areas, woman are still highly perceived as unfit to be in political world. Keywords: Gender, politics, media, framing.